Replacing defective thymus function. Issue 6 (December 2020) - Kreins, Alexandra Y.; Graham Davies, E.
Abstract : Purpose of review: Transplantation of cultured postnatal allogeneic thymus has been successful for treating athymia, mostly associated with complete DiGeorge syndrome, for more than 20 years. Advances in molecular genetics provide opportunities for widening the range of athymic conditions that can be treated while advances in cell culture and organ/tissue regeneration may offer the prospect of alternative preparations of thymic tissue. There are potential broader applications of this treatment outside congenital athymia. Recent findings: At the same time as further characterization of the cultured thymus product in terms of thymic epithelial cells and lymphoid composition, preclinical studies have looked at de-novo generation of thymic epithelial cells from stem cells and explored scaffolds for delivering these as three-dimensional structures. In the era of newborn screening for T-cell lymphopaenia, a broadening range of defects leading to athymia is being recognized and new assays should allow differentiation of these from haematopoietic cell defects, pending their genetic/molecular characterization. Evidence suggests that the tolerogenic effect of transplanted thymus could be exploited to improve outcomes after solid organ transplantation. Summary: Thymus transplantation, the accepted standard treatment for complete DiGeorge syndrome is also appropriate for other genetic defects leading to athymia. Improved strategies for generating thymus may lead to better outcomes and broader application of this treatment.